Pengaruh Independensi dan Profesionalisme Auditor terhadap Kualitas Audit - Putri Nugraheni Cahyaning R; Anisa Ari Suci (Akuntansi, 2024)
This study examines the influence of auditor independence and professionalism on audit quality within the business environment. Auditor independence and professionalism are identified as key factors affecting accurate and reliable audit outcomes. When assessing independence, the study considers the auditor's autonomy in decision-making, free from influence by other involved parties. Meanwhile, professionalism is measured by the auditor's ability to carry out tasks in accordance with ethical standards and relevant knowledge in their field. The research methodology adopts an analytical approach to understand the impact of independence and professionalism on audit quality. The analysis results demonstrate that higher independence enhances audit quality by promoting more objective and precise reporting. High levels of professionalism also contribute to better audit quality, highlighting the significance of adhering to ethical standards and possessing in-depth knowledge for effective auditing. This research reaffirms the significant roles of auditor independence and professionalism in determining audit quality. The implications of these findings underscore the need to focus on these factors in audit practices to ensure the reliability of audit outcomes.